Repurposing of the Open Access Malaria Box for Kinetoplastid Diseases Identifies Novel Active Scaffolds against Trypanosomatids. (June 2015) - Kaiser, Marcel; Maes, Louis; Tadoori, Leela Pavan; Spangenberg, Thomas; Ioset, Jean-Robert
Phenotypic screening had successfully been used for hit generation, especially in the field of neglected diseases, in which feeding the drug pipeline with new chemotypes remains a constant challenge. Here, we catalyze drug discovery research using a publicly available screening tool to boost drug discovery. The Malaria Box, assembled by the Medicines for Malaria Venture, is a structurally diverse set of 200 druglike and 200 probelike compounds distilled from more than 20, 000 antimalarial hits from corporate and academic libraries. Repurposing such compounds has already identified new scaffolds against cryptosporidiosis and schistosomiasis. In addition to initiating new hit-to-lead activities, screening the Malaria Box against a plethora of other parasites would enable the community to better understand the similarities and differences between them. We describe the screening of the Malaria Box and triaging of the identified hits against kinetoplastids responsible for human African trypanosomiasis ( Trypanosoma brucei ), Chagas disease ( Trypanosoma cruzi ), and visceral leishmaniasis ( Leishmania donovani and Leishmania infantum ). The in vitro and in vivo profiling of the most promising active compounds with respect to efficacy, toxicity, pharmacokinetics, and complementary druggable properties are presented and a collaborative model used as a way to accelerate the discovery process discussed.